Notes on the Neotropical leafhopper subgenus Amplicephalus (Nanctasus) Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with description of two new species - Duan, Yani; Dietrich, Christopher H. (Zootaxa, 2018)
Morphological characters previously used to define the subgenus Amplicephalus (Nanctasus) Linnavuori and its status are discussed. Two new species are described and illustrated, and tentatively placed in subgenus A. (Nanctasus) Linnavuori: A. (N.) anayensis sp. n. and A. (N.) paralbivenosus sp. n. A checklist and a key to species of the subgenus are provided.